2008
DOI: 10.1016/j.pec.2007.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a multimedia CD-ROM for exercise during pregnancy and postpartum

Abstract: Objective-To meet the need for an interactive product on exercise during pregnancy and postpartum, we developed and evaluated a personally-tailored multimedia CD-ROM.Methods-Pregnant and postpartum women, who were randomly assigned to either the experimental group (PregXercise™ CD-ROM) or the control group (CD-ROM with neutral content), navigated through the CD-ROM for 1 hour. Main outcomes were exercise self-efficacy and knowledge.Results-In analyses of covariance, compared with the control group, the experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 24 publications
1
21
1
Order By: Relevance
“…These strategies help persuade participants that they are capable of coping with childbirth'' [46]. Therefore, the educational software program can increase the knowledge of the pregnant women regarding labor and behaviors for coping with labor pain and promotes their self-efficacy in the face of stressful situations [36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These strategies help persuade participants that they are capable of coping with childbirth'' [46]. Therefore, the educational software program can increase the knowledge of the pregnant women regarding labor and behaviors for coping with labor pain and promotes their self-efficacy in the face of stressful situations [36].…”
Section: Discussionmentioning
confidence: 99%
“…An intervention study was developed by Hausenblas et al [36] which evaluated a multimedia CD-ROM for exercise during pregnancy and postpartum. The results of this study showed that the participants who received multimedia CD-ROM training reported significantly higher self-efficacy and exercise knowledge as compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patient training, multimedia technology has been widely used to increase understanding of suitable self-care activities to control disease symptoms such as diabetes (18,19), asthma (20), cancer (21), pregnancy (22), and colonoscopy (23). The effectiveness of multimedia technology in diabetic patients has been variable.…”
Section: Introductionmentioning
confidence: 99%